Sequencing and analysis of the complete mitochondrial genome of tundra shrew (Sorex tundrensis) from China. (3rd July 2016) - Xu, Chunzhu; Zhao, Shuai; Wu, Hualin; Wu, Shengyang; Zhang, Zhongwen; Wang, Bo; Dou, Huashan
Abstract: The complete mitogenome sequence of tundra shrew ( Sorex tundrensis ) was determined using long PCR. The genome was 17, 444 bp in length and contained 13 protein-coding genes, 2 ribosomal RNA genes, 23 transfer RNA genes, 1 origin of L strand replication and 1 control region. The overall base composition of the heavy strand is A (32.9%), C (24.8%), T (29.0%), and G (13.3%). The base compositions present clearly the A–T skew, which is most obviously in the control region and protein-coding genes. The extended termination-associated sequence domain, the central conserved domain and the conserved sequence block domain are defined in the mitochondrial genome control region of tundra shrew. Mitochondrial genome analyses based on MP, ML, NJ and Bayesian analyses yielded identical phylogenetic trees. The three Sorex species formed a monophyletic group with the high bootstrap value (100 %) in all examinations.